Effect of technology-supported mindfulness-based interventions for maternal depression: a systematic review and meta-analysis with implementation perspectives for resource-limited settings - Bekelu Teka Worku; Misra Abdulahi; Demissew Amenu; Bruno Bonnechère (BMC Pregnancy and Childbirth)
Abstract Background Maternal depression is pregnancy and childbirth-related depression during pregnancy (prenatal depression (PND)) or after delivery (postpartum depression (PPD)). It is a recognized global public health concern with extensive repercussions adversely affecting women’s well-being and the developmental progress of infants. Mindfulness-based interventions (MBIs) have been shown to be effective in maternal depression. Technology-supported MBI could be an effective preventive strategy for maternal depression, especially in low- and middle-income countries (LMICs) where lack of important resources limits the accessibility to standard care. However, the limited available studies assessing the effect of technology-supported MBIs for maternal depression might be insufficient to reach a definitive conclusion. This systematic review aimed to evaluate the pooled estimated effect of technology-supported MBIs for maternal depression, identify available studies, and reveal applicable health technologies with MBIs. Method This study was conducted according to the PRISMA-P 2020 and the review protocol was registered in PROSPERO; CRD42024537853. The risk of bias was evaluated using the PEDro scale. The meta-analysis was done with R. Result Data from 18 articles, none from low-income countries (LICs), were included in the systematic review, representing 2,481 participants, 15 studies were included in the meta-analysis. The pooled effect size indicated that technology-supported MBIs had a positive effect on maternal depression (SMD − 0.55, 95% CI [− 0.70; −0.40], p < 0.001). The sub-group analysis showed that this intervention was effective in both PND (SMD = − 0.57, 95% CI [− 0.74; −0.39], p < 0.001) and PPD (SMD − 0.53, 95% CI [− 0.91; −0.15], p = 0.014). Conclusion Integrating technology-supported MBIs into maternal care is recommended to enhance maternal mental health. However, the lack of trials in LMICs may limit the generalizability and external validity of this finding and it is crucial to conduct further research, in the area to tailor intervention and maximize its effectiveness. Context-specific trial studies are pivotal for successful program adoption.